Evaluation of antioxidant potential and anti-diabetic effect of ethanol seed extract of Garcinia kola (Bitter Kola) in albino rat - Omodamiro, O.D.; Ajah, O.; Ewa-ibe, C. (Journal of Medicinal Herbs and Ethnomedicine, 2020)
The medicinal properties of plants have been investigated in the recent scientific world because of their potent antioxidant activities, mild side effects and economic viability. This study evaluated the antioxidant property and antidiabetic effect of ethanol seed extract of G. kola (bitter kola) on alloxan induced diabetic albino rats. The in-vitro antioxidant assay was done using standard methods. Thirty (36) albino rats were used for the in-vivo study and fasted for 16-18hours and thereafter induced diabetes with 150mg/ kg b.w. of alloxan monohydrate via intraperitoneal injection. The animals were divided into six groups of six (6) rats each. Group A was the normal control, group B was the positive control (treated with 5mg/kg b.w of glabeclamide), Group C was the negative control (untreated) and groups D through F were administered 500mg/kg, 250mg/kg and 125mg/kg of the extract respectively. The results showed 49.70% reduction in blood glucose level of the 500mg/kg extract treated group compared to the positive control (45.03 %) on the day 7. The antioxidant results showed a significant (p<0.05) dose dependent increase in its ability to scavenge free radicals. The results of this study suggested the use of G. kola seed for the treatment of free radical mediated diseases and management of diabetes.